Investigation of agro-byproduct pellet properties and improvement in pellet quality through mixing. (1st January 2020) - Park, Sunyong; Kim, Seok Jun; Oh, Kwang Cheol; Cho, Lahoon; Kim, Min Jun; Jeong, In Seon; Lee, Chung Geon; Kim, DaeHyun
Abstract: In this study, pellets made from agricultural byproducts were evaluated and the possibility of their conversion into fuel was investigated. Conventional wood pellets were used as the control, and pepper, perilla, rice chaff, and spent coffee ground were molded into pellets and evaluated based on various parameters such as size, bulk density, and calorific value following the standard for "non-wood pellets" and "resource conservation and recycling promotion laws." The perilla or rice chaff pellets were determined as bio-solid refused fuel (Bio-SRF) grade because of low durability. Agricultural byproduct (pepper, perilla, and rice chaff) pellets were mixed with spent coffee ground to improve their properties. They were molded into pellets and evaluated based on the above standards. Pepper + coffee (PCP) pellets had lower chlorine content than pepper pellets but copper content was higher. Rice chaff + coffee (CCP) pellets had slightly higher durability, but the bulk density was decreased. Therefore, CCP was determined as Bio-SRF. Perilla + coffee pellets (PRCP) were determined as A grade owing to higher durability. Thus, it was confirmed that agricultural byproducts could be used as viable energy sources by mixing them. Highlights: This study evaluated the properties of pellets produced from agro-byproducts. Coffee waste, chaff, perilla stem, and pepper stem pellets were considered. Each pellet was evaluated as Grade-A/B or Bio-SRF as per KEAA standards. Chaff, perilla, and pepper stem were mixed with 50% coffee waste and evaluated. The mixed pellets (except coffee + chaff) were superior to the individual pellets.